Security Threats in Today's Payment Processing and Advanced Technological Solution - Rajesh Kotha (North American Journal of Engineering Research, 2023)
Recent advancements in information technology have brought numerous complications that put the financial processing systems at risk, hence, many safety challenges that current payment systems experience in the emerging digital economy. This paper focuses on the top security risks like data loss and payment fraud and the new technological approaches of data encryption, tokenization, and fraud detection by an artificial intelligence system. Encryption encodes the payment information so that unauthorized persons cannot intercept their contents, and tokenization replaces regular payment information with tokens, making hacking difficult. A fraud detection system based on AI applies machine learning techniques to stop fraudulent actions in real-time. This word examines the challenges hampering the implementation of these technologies. The paper further analyzes the uses of security threats. The final section of the paper explores the scope of the solutions studied. This paper concludes by asserting that implementing tech-based solutions to security risks ensures the trust of the masses in digital payment systems.